ANALISIS METODE OHLSON DALAM MEMPREDIKSI KEBANGKRUTAN PADA PERUSAHAAN LQ 45 - Shita Tiara; Debbi Chyntia Ovami (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2019)
This study aims to determine the effective or not ohlson method in predicting bankruptcy in the LQ-45 company listed on the Indonesia Stock Exchange (IDX). The type of research in this study is qualitative. The subjects in this study were LQ-45 companies listed on the Indonesia Stock Exchange during the 2014-2016 period. The object in this study were 30 companies selected based on the criteria needed for final data totaling 90 financial statements. The data source in this study is secondary data downloaded through www.idx.co.id. The data analysis technique in this study used qualitative descriptive analysis. The results of this study indicate that LQ-45 companies listed on the Indonesia Stock Exchange suffered bankruptcy by 84% of the total objects, namely 30 companies. Companies that experienced bankruptcy as many as 25 and companies that did not experience bankruptcy based on the Ohlson method were only 5 companies. From these results Olhlson was declared effective in predicting bankruptcy where the range of 80% of the total objects had been passed by Ohlson where Ohlson reached 84%.